Exports, Imports, and Growth Nexus in Bangladesh: Facts from Causality and Cointegration Analysis - Hassan, Md. Mahmudul (Economic Journal of Nepal, 2014)
Export and import play an important role in economic development and growth. Accordinglythe importance of these variables is a field of research. This paper uses a theoreticallyconsistent technique to investigate legitimacy of the export led growth (ELG) hypothesis forBangladesh considering the variable import as well. The paper investigates the Grangercausalitytest among exports, imports, and economic growth in Bangladesh over the period1980-2011 as well as the modern cointegration test also. The outcome of the study exists nolong run relation between the variables and so no short run relation as well. The causalitytest finds one way causality running from export to GDP indicating the victory of ELGhypothesis for Bangladesh. The Economic Journal of Nepal, Vol. 34, No. 4, October-December 2011 (Issue N0. 136)